Validation of an apicoplast genome target for the detection of Plasmodium species using polymerase chain reaction and loop mediated isothermal amplification. (July 2015) - Oriero, C.E.; van Geertruyden, J.-P.; Jacobs, J.; D'Alessandro, U.; Nwakanma, D.
Abstract: The genome of the Plasmodium apicoplast, which has a higher copy number compared with current targets for molecular diagnosis of malaria, appears to be a suitable target for detection of submicroscopic infections that are capable of sustaining transmission. Novel primers targeting a conserved segment of the apicoplast (PFC10_AP|0010:rRNA) were designed and used in a number of different high throughput platforms such as single-step PCR (ssPCR), nested PCR (nPCR) and loop-mediated isothermal amplification (LAMP) for parasite detection. Replicates of ten-fold serial dilutions of Plasmodium falciparum 3D7 DNA, with equivalent parasite density ranges of 200 000 to 0.2 parasites/μL, were used to determine the limit of detection and repeatability of each assay. A panel of 184 archived DNA samples extracted from either EDTA whole blood or dried blood spots, from across West Africa and South East Asia was used to determine the diagnostic performance of the assays. All assays amplified the 2 parasites/μL dilution except the ssPCR, which amplified two of the three replicates. Using an 18S rRNA PCR as reference, the sensitivity was 98% (95% CI 93–100%) for the LAMP assay, 87% (95% CI 79–93%) for ssPCR and 100% (95% CI 97–100%) for nPCR. Specificity was 91% (95% CI 83–96%) for LAMP, 82% (95% CI 72–90%) for ssPCR and 66% (95% CI 54–76%) for nPCR. The apicoplast genome-based nPCR detected more positive samples overall than the reference method. Discrepant samples were confirmed as true positives using a probe-based real-time quantitative PCR assay. The results show that the apicoplast genome is a suitable target for molecular diagnosis of malaria.